2022
DOI: 10.31384/jisrmsse/2022.20.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Human Resource Practices and Employee Performance: Mediating Role of Work Engagement and Training Sessions

Abstract: The current study is an empirical evaluation of Human Resource (HR) practices on employee Performance within Pakistani organisations via the mediating role of work engagement and training sessions as they are conducted to enhance their performance in line with human capital theory. For the research, data was collected from 259 employees and HR managers from Pakistan manufacturing and service sector through self administered questionnaire. Moreover, two statistical software, SPSS and AMOS, have been employed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Employees' knowledge, skills and competencies are a crucial prerequisite for the effective and efficient functioning of diverse organizational activities (Irawan, Bastian, & Hanifah, 2019;Ngwa, Adeleke, Agbaeze, Ghasi, & Imhanrenialena, 2019;Turulja & Bajgoric, 2018). Amir, Ali, Ali, and Ali (2022) postulate that employee performance provides specialized human elements with competence that enhance organizational effectiveness. The following hypothesis is proposed: H4.…”
Section: Employee Performance and Organizational Effectivenessmentioning
confidence: 99%
“…Employees' knowledge, skills and competencies are a crucial prerequisite for the effective and efficient functioning of diverse organizational activities (Irawan, Bastian, & Hanifah, 2019;Ngwa, Adeleke, Agbaeze, Ghasi, & Imhanrenialena, 2019;Turulja & Bajgoric, 2018). Amir, Ali, Ali, and Ali (2022) postulate that employee performance provides specialized human elements with competence that enhance organizational effectiveness. The following hypothesis is proposed: H4.…”
Section: Employee Performance and Organizational Effectivenessmentioning
confidence: 99%
“…Quresh et al (2016) found that all the tested variables (selection, training, performance evaluation system, compensation system, and employee participation) correlate with banks' financial performance. This underscores the importance of the HR department in optimizing employee performance by providing qualified professionals whose impact is felt throughout the organization (Amir et al, 2022). Therefore, it is imperative for companies to continually improve their HR strategies to remain competitive in the market, especially in highly competitive industries (Hee & Jing, 2018).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…When we turn our lens to work engagement, it can be seen that myriad factors affect work engagement levels of employees. Motivation enhancing human resources practices (Amir et al, 2022 ; Beltrán-Martín et al, 2022 ) and value match between an individual and an organization (Okolie, 2022 ) are considered as significant antecedents of work engagement. According to social identity theory, when individuals work in an organization with responsible practices they are proud of, their identification with their organziation increases (Yang et al, 2021 ).…”
Section: Hypothesismentioning
confidence: 99%